2016
DOI: 10.1038/srep33306
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Angular Momentum-based Space Division Multiplexing for High-capacity Underwater Optical Communications

Abstract: To increase system capacity of underwater optical communications, we employ the spatial domain to simultaneously transmit multiple orthogonal spatial beams, each carrying an independent data channel. In this paper, we show up to a 40-Gbit/s link by multiplexing and transmitting four green orbital angular momentum (OAM) beams through a single aperture. Moreover, we investigate the degrading effects of scattering/turbidity, water current, and thermal gradient-induced turbulence, and we find that thermal gradient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 187 publications
(80 citation statements)
references
References 55 publications
2
68
0
Order By: Relevance
“…of the beam's profile [26,34]. The aberrations in the beam are often visible in the intensity of the beam; however, more precise information lies in the phase of the received beam.…”
Section: Resultsmentioning
confidence: 99%
“…of the beam's profile [26,34]. The aberrations in the beam are often visible in the intensity of the beam; however, more precise information lies in the phase of the received beam.…”
Section: Resultsmentioning
confidence: 99%
“…Baghdady et al performed experimental demonstration of a 3 Gbit/s underwater communication link, using two 445 nm lasers, and successfully transmitted the signal over a distance of 2.94 m modulated on a simple on-off keying non-return to zero (OOK-NRZ) scheme [134]. In [135], Ren et al reported an aggregated data rate of 40 Gbit/s, using 4 green OAM modes over 1.2 m of turbulent tap water. Each of the four beams carried a 10 Gbit/s signal generated by doubling the frequency of the data signal, at 1064 nm (infrared light).…”
Section: Underwater Communicationmentioning
confidence: 99%
“…13,14 To assess the feasibility of such OAM multiplexing in an underwater communications channel it is important to analyse the degree of observed channel degradation induced by flowing water in real Oceanic conditions. In this paper we present a study of measured inter-channel crosstalk for a set of OAM modes propagating through 3m of slowly flowing water, similar to that found in Oceanic conditions.…”
Section: 12mentioning
confidence: 99%